A Critical Analysis of the Stand-By Arrangements of the International Monetary Fund. - Ogan, Comban Adrien (Obafemi Awolowo University, 2014)
The controversy over the suitability or otherwise of IMF economic programmes to underdeveloped countries has been exacerbated by the unprecedented debt problems facing those countries from the 1970s onwards, with the attendant legal and socio-political consequences. Yet, the issues surrounding IMF economic policies have traditionally been left to economists, to the exclusion of lawyers, despite the important legal problems involved, and despite the emergence of international economic and monetary law as a special branch of general international law. The present thesis makes use of the methodology evolved by this relatively new discipline to inquire into one of the most ingenious developments in international economic activists of recent times: the IMF stand-by arrangement.